Prevalence of bedaquiline resistance in patients with drug-resistant tuberculosis: a systematic review and meta-analysis - Xinyang Hu; Zhiwei Wu; Jing Lei; Yanqin Zhu; Jingtao Gao (BMC Infectious Diseases)
Abstract Background Drug-resistant tuberculosis (TB) remains a major global public health challenge. While bedaquiline (BDQ) offers improved treatment outcomes for patients with multi-drug resistant TB (MDR-TB), its widespread use has led to the emergence of BDQ resistance. Methods This systematic review evaluated the prevalence of BDQ resistance among adult patients through searches of PubMed, Web of Science, and Embase databases. Sensitivity and subgroup analyses were performed to explore sources of heterogeneity and compare prevalence estimates across groups. The Joanna Briggs Institute’s quality assessment checklist was used to evaluate the methodological quality of the included studies. Heterogeneity between studies was evaluated using Cochran’s Q and I 2 tests.This study is registered with PROSPERO, CRD42024620791. Results The weighted average prevalence of BDQ resistance was 5.7% (95% CI: 3.6–8.3), with acquired resistance reported at 5.4%. Geographic differences were observed, with South Africa showing a higher prevalence (10.4%) compared to China (2.4%).High-quality studies reported a prevalence of 5.2%, while fair-quality studies reported 7.7%. Mutations in the Rv0678 gene represented a significant proportion, reaching as high as 65.6%. Conclusions Our findings highlight an increasing trend in acquired resistance to BDQ, offering critical insights for managing MDR-TB. The application of whole-genome sequencing shows promise for advancing understanding of drug resistance mechanisms in Mycobacterium tuberculosis.